Răspuns :
a+b+c=19692
b=3*a+6932
c=2*a+12700
a+3*a+6932+2*a+12700=19692
a+3*a+2*a+19632=19692
a+3*a+2*a=60
a*(1+3+2)=60
a*6=60
a=60:6=10
b=3*a+6932
c=2*a+12700
a+3*a+6932+2*a+12700=19692
a+3*a+2*a+19632=19692
a+3*a+2*a=60
a*(1+3+2)=60
a*6=60
a=60:6=10
a+b+c=19 692
b=(a*3)+6932
c=(a*2)+12 700
---------------------
a=?; b=? ;c=?
a+((a*3)+6 932)+((a*2)+12 700)=19 692
a+(3a+6 932)+(2a+12 700)=19 692
6a+6 932+12 700=19 692
6a+19 632=19 692
6a=19 692-19 632
6a=60
a=60:2
a=10
10+((10*3)+6 932)+((10*2)+12 700)=19 692
10+(30+6 932)+(20+12 700)=19 692
10+6 962+12 720=19 692
a=10
b=6 962
c=12 720
b=(a*3)+6932
c=(a*2)+12 700
---------------------
a=?; b=? ;c=?
a+((a*3)+6 932)+((a*2)+12 700)=19 692
a+(3a+6 932)+(2a+12 700)=19 692
6a+6 932+12 700=19 692
6a+19 632=19 692
6a=19 692-19 632
6a=60
a=60:2
a=10
10+((10*3)+6 932)+((10*2)+12 700)=19 692
10+(30+6 932)+(20+12 700)=19 692
10+6 962+12 720=19 692
a=10
b=6 962
c=12 720